Individualization in swimming and a way of preparation for Olympic Games - Kopchikova, S.G. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to analyze the high-end training swimmers who specialize in complex navigation. Material : Ukraine national team members from different years of training, swimmers high class of 50 people. A review of questionnaires and coaches of the national team of Ukraine to the XXVIII Olympic Games in Athens. Results found that athletes training and competitive activities differ in structure and content compared to previous preparation for the Olympic Games. In the 2004 Olympic champion set, the largest amount of work is 2520 km with the largest number of events in that year. It is indicated that the athlete in the first 4 years of preparation for his first Olympics gradually increasing annual volume and intensity of training loads. Over the next 4 years - the number of competitions, including commercial. An important factor in this stage is moral and strong-willed and psychological preparation. Conclusions : preparing athletes for major competitions at the stage of conservation achievements is narrowly focused specialized nature, depending on the age of the athlete, his specialization, gender, duration of phase conservation achievements.